Configuration optimisation of tuned mass inerter absorbers for cable vibration suppression considering experimentally identified parasitic effects - Zhang, Sara Ying; Li, Deyuan; Zhu, Qi; He, Haonan; Li, Yiyuan (Elsevier, 2026)
Traditional cable vibration control mainly relies on dampers, whose effectiveness is often limited by their installation position. Tuned mass dampers can improve performance, but require additional mass. More recently, inerters have been introduced to further enhance vibration mitigation performance, with the tuned mass damper inerter being the most notable example. However, only a limited subset of possible tuned mass inerter absorber layouts – comprising a reaction mass and a number of springs, dampers, and inerters – has been explored. In addition, parasitic nonlinearities in practical implementations are often neglected, leaving their influence on performance prediction unclear. This study presents a systematic synthesis and optimisation framework of tuned mass inerter absorbers for cable vibration control. Generic immittance-function networks are used to generate and evaluate all feasible layouts under the component constraints, while experimentally identified parasitic effects are incorporated. A finite element cable model is developed, and the robustness of the proposed absorber is assessed under seismic and wind loading. The results show that the optimal configuration outperforms conventional tuned mass damper and tuned mass damping inerter, reducing maximum cable displacement by up to 33.1% and 7.9%. The refined design also limits the performance loss caused by parasitic effects to less than 5.4%.
Keywords: 40 Engineering; 4017 Mechanical Engineering; 7 Affordable and Clean Energy; Applied Mathematics; Tuned mass inerter absorber; Generic immittance-function networks; Cables; Parasitic effects